Serotonergic Antidepressants and Risk for Traumatic Intracranial Bleeding - Isokuortti Harri; Iverson Grant L; Posti Jussi P; Ruuskanen Jori O; Brander Antti; Kataja Anneli; Nikula Milaja; Öhman Juha; Luoto Teemu M (Switzerland, 2022)
Background:
Serotonergic antidepressants may predispose to bleeding but the effect on traumatic intracranial bleeding is unknown.
Methods:
The rate of intracranial bleeding in patients with antidepressant medication was compared to patients not antidepressants in a cohort of patients with acute head injury. This association was examined by using a consecutive cohort of head trauma patients from a Finnish tertiary center emergency department (Tampere University Hospital, Tampere, Finland). All consecutive (2010–2012) adult patients (n = 2,890; median age = 58; male = 56%, CT-positive = 22%, antithrombotic medication users = 25%, antidepressant users = 10%) who underwent head CT due to head trauma in the emergency department were included.
Results:
Male gender, GCS <15, older age, and anticoagulation were associated with an increased risk for traumatic intracranial bleeding. There were 17.8% of patients not taking antidepressants and 18.3% of patients on an antidepressant who had traumatic intracranial bleeding (p = 0.830). Among patients who were taking antithrombotic medication, 16.6% of the patients not taking antidepressant medication, and 22.5% of the patients taking antidepressant medication, had bleeding (p = 0.239). In a regression analysis, traumatic intracranial hemorrhage was not associated with antidepressant use.
Conclusions:
Serotonergic antidepressant use was not associated with an increased risk of traumatic intracranial hemorrhage.